Large Multimeric Assemblies of Nucleosome Assembly Protein and Histones Revealed by Small-angle X-ray Scattering and Electron Microscopy - Newman, Emily R. (American Society for Biochemistry and Molecular Biology, 2012)
The nucleosome assembly protein (NAP) family represents a key group of histone chaperones that are essential for cell viability. Several x-ray structures of NAP1 dimers are available; however, there are currently no structures of this ubiquitous chaperone in complex with histones. We have characterized NAP1 from Xenopus laevis and reveal that it forms discrete multimers with histones H2A/H2B and H3/H4 at a stoichiometry of one NAP dimer to one histone fold dimer. These complexes have been characterized by size exclusion chromatography, analytical ultracentrifugation, multiangle laser light scattering, and small-angle x-ray scattering to reveal their oligomeric assembly states in solution. By employing single-particle cryo-electron microscopy, we visualized these complexes for the first time and show that they form heterogeneous ring-like structures, potentially acting as large scaffolds for histone assembly and exchange.